In times of uncertainty: do temporary workers have the intention and willingness to become entrepreneurs? - Costa, Sílvia Fernandes; Caetano, António; Santos, Susana Correia (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Temporary workers are an increasingly representative group in the labour market. They work in precarious situations and are aware that stability and predictability of employment are no longer guaranteed. Entrepreneurship may be an alternative for these workers, even in the form of self-employment. The purpose of this study is to analyse the entrepreneurial intentions and the willingness to consider entrepreneurship as a career option by temporary workers. Specifically, we aim to analyse the self-perception of entrepreneurial competencies of a group of temporary workers. Drawing from our results we conclude that the self-perception of different levels of entrepreneurial competencies is associated with different intentions and willingness to considering entrepreneurship as a career option. This study is a first step in understanding how temporary workers in a changing labour market perceive entrepreneurship as well as their skills to engage in entrepreneurial activities as a career option.